TRENDS IN THE WORK OF THE INTERNATIONAL COURT OF JUSTICE IN 2013–2017 - Konstantin V. Timokhin (Московский журнал международного права, 2018)
INTRODUCTION. The work of the International Court of Justice is the benchmark not only for other international courts and tribunals but also for the States which with rapt attention follow its decisions, though formally these verdicts are binding only for the Parties to the dispute. Evidently each ICJ case goes far beyond the bounds of a bilateral dispute and Court's conclusions are more general in nature thus being applicable to other situations.MATERIALS AND METHODS. In the Article the practice of the International Court of Justice for the previous five years starting from 2013 till 2017 is researched: both the cases, which the International Court had reviewed and in respect of which pronounced its verdict in the last five years, and the cases which had been in the docket of the Court by the end of 2017 are analysed. Apart from this the author also looks at the previous practice of the Court with an aim of pinpointing the tendencies in ICJ work. Further more, the Article is furnished with the statistical data which helps to better appreciate the “price” of the efforts of the Court to promote the development of international law and resolve challenges which it is confronted with.RESEARCH RESULTS. The Article demonstrates that the Court's practice highlights many of the current world's most outstanding problems and shows how States perceive possible solutions thereof. The author comes to a conclusion that the work of the International Court of Justice demonstrates high demand in its services and also proves it to be an influential authority in matters of high complexity and sensitivity. The Court manages to be an objective and efficient body using international law to advance stability on international arena.DISCUSSION AND CONCLUSIONS. As a conclusion the article provides some of the recent and most prominent trends in the Court's practice. Among them are the higher demand for the provisional measures to be established by the Court in cases of crises, disputes with regard to the jurisdiction of the Court becoming “standard”, an increasing amount of attempts for the revision of the Court's verdicts (or their interpretation), growing external pressure, endeavours to politicize its work, and a corresponding, as it seems, increase in discord between the ICJ Judges.